2018
DOI: 10.3390/inorganics6040126
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Copper Intracellular Chelation as an Anticancer Drug Strategy

Abstract: A very promising direction in the development of anticancer drugs is inhibiting the molecular pathways that keep cancer cells alive and able to metastasize. Copper and iron are two essential metals that play significant roles in the rapid proliferation of cancer cells and several chelators have been studied to suppress the bioavailability of these metals in the cells. This review discusses the major contributions that Cu and Fe play in the progression and spreading of cancer and evaluates select Cu and Fe chel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 227 publications
3
58
0
Order By: Relevance
“…The greater activity of the flowering top extract may depend on its strong ferrous ions chelating properties. Indeed, it has been shown that some metals, such as copper and iron, play a significant role in the rapid proliferation of cancer cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…The greater activity of the flowering top extract may depend on its strong ferrous ions chelating properties. Indeed, it has been shown that some metals, such as copper and iron, play a significant role in the rapid proliferation of cancer cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…Specificity in cancer cell targeting is also important and such approaches are considered to have a better therapeutic outcome. The efficacy and risk/benefit assessments of such combination approaches which may involve metal ions and chelators is in progress, with some of these at an investigational level and others in different stages of clinical development and use [1,4,5].…”
Section: Examples Of the Clinical Applications Of Chelator Metal Compmentioning
confidence: 99%
“…The therapeutic strategies for targeting cancer cell growth and proliferation by chelators may involve the modulation of protein function or other associated pathways such as the inhibition of key enzymes e.g., the iron containing ribonucleotide reductase involved in DNA synthesis, incorporation of xenobiotic metals such as Ga which could bind to nucleotide substrates and also disrupt iron and other essential metal metabolic pathways and lysosomic damage by redox active metal complexes (Table 1) [1,[4][5][6]. Chelating drugs could also be used in many other anticancer approaches such as modulation of macrophage anticancer function and also in the protection from the cardiotoxicity of anticancer drugs [7][8][9].…”
Section: Examples Of the Clinical Applications Of Chelator Metal Compmentioning
confidence: 99%
“…[54] Intracellular chelation as a strategy to induce cancer cell death was particularly studied during the last years. [55] Consequently, the discovery of new compounds with such a transchelation ability becomes an alternative strategy to develop potent anticancer drugs.…”
Section: Zinc and Iron Coordination And Transchelation Studiesmentioning
confidence: 99%
“…To sum up, we suggest that the notable cytotoxic activity of the compounds could be due, at least partially, to the dysregulation of iron and/or copper homeostasis which, in turn, could induce, for example, perturbation of cell cycle and reactive oxygen species (ROS) generation. [55]…”
Section: Cytotoxicity Versus Iron Coordinationmentioning
confidence: 99%